EDITORIAL - Mariano, A. B. (Revista de Engenharia Térmica, 2014)
The population growing awareness regarding the use of fossil fuels, especially with respect to correlated environmental issues, led to an increased interest in renewable energy sources in the last decade. Around 200 years ago, biomass lost its historic leadership as a source for coal production. Next, it was seen the rapid growth in the use of petroleum and natural gas, and in this way, the use of biomass was limited particularly to agricultural regions. Currently, due to the responsible use of forests and large areas of reforestation, the use of biomass has conquered international attention and the demand for using wood-based materials is increasing. The biomass is not restricted to wood products, but also to any product of biological origin, which could be utilized as fuel, or for other industrial purpose and, in addition, has the advantage of being renewable. The existing challenges are the development of efficient productive chains around a product and total use of the material, including the use of the generated residuals, and the verticalisation of industrial plants. Therefore, the Thermal Engineering community could contribute to the development of technologies for coupling processes such as conversion of residuals into products of commercial value or their use for power generation. There is much opportunity for improvement in the wood, sugar cane or soybean industries, considering that all of them use heat to convert the substrates into products. Replacing natural gas or electricity used to generate heat by renewable sources such as residual biomass pellets without loss of efficiency could greatly increase the energetic efficiency of a plant, as well as reduce environmental impact.